Effects of a Standard Dose of Fresh Frozen Plasma on Various Elevations in the International Normalized Ratio - Emine Akıncı; Şeref Kerem Çorbacıoğlu; Oğuz Yardım; Hüseyin Uzunosmanoğlu; Yunsur Çevik (Eurasian Journal of Emergency Medicine, 2016)

(untitled)
Aim: This study aimed to determine the effects of using a standard dose of fresh frozen plasma (FFP) on the international normalized ratio (INR) of patients with various elevations in INR from using warfarin.Materials and Methods: This prospective study was conducted in the emergency department (ED) of a training and research hospital from February 2015 to January 2016 with patients who presented with elevated INRs from using warfarin. Their demographic data, clinical features, and laboratory findings, including pre- and post-transfusion INRs, were recorded. The standard dose of FFP used was 3 units of FFP (900 mL). Delta INR (ΔINR) was defined as the pre-transfusion INR minus the post-transfusion INR. Two hours after the end of the FFP transfusion, each patient’s INR was measured again.Results: Thirty-two patients who received FFP and whose pre- and post-transfusion INRs were measured were included. Of these 32 patients, 23 (71%) were women, and the patients’ mean age was 72.8±11.1. The mean pre- and post-transfusion levels and ΔINR were 10.6±5.3, 4.3±2.3, and 6.2±4.3, respectively. There was a strong positive correlation between high pre-transfusion INR and ΔINR (p<0.001, r=0.85). Regression analysis performed to estimate ΔINR after the transfusion of a standard dose of FFP found that ΔINR=0.69×(pre-transfusion INR) -1.111 (p<0.001).Conclusion: The present study found that using a standard dose of FFP caused varying reductions in ΔINRs that correlated with the pre-transfusion INR.